Healthcare waste management practices and associated factors among healthcare workers in Sub-Saharan Africa: A systematic review and meta-analysis - Gete Berihun; Zebader Walle; Belay Desye; Chala Daba; Abebe Kassa Geto; Lake Kumlachew; Leykun Berhanu (PLoS ONE, 2025)
Introduction Inadequate management of healthcare waste present significant health hazards to healthcare workers, patients, waste handlers, and the whole communities, especially in developing countries. Although various primary studies have been conducted in different countries across the continent, there has been no comprehensive research examining healthcare waste management practices in Sub-Saharan Africa. Objective This review aimed to assess healthcare waste management practices and associated factors among healthcare workers in Sub-Saharan Africa. Methods and materials This systematic review and meta-analysis were performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA 20) guidelines. PubMed, Science-Direct, Google Scholar, Hinari, and Google databases were used to find essential literature. The extracted data were analyzed using statistical software, STATA version 14. Publication bias was assessed using the Egger test and funnel plot, whereas heterogeneity was assessed using the I2 statistic. Results This review include 29 studies comprising 7588 participants. The pooled estimate of good healthcare waste management practices among participants was 49.74% (95% CI: 43.73–55.76) (I2 = 96.8%, P < 0.000). Sex, knowledge, training on healthcare waste management, use of working manuals/guidelines, and working hours were factors significantly associated with healthcare waste management practices among healthcare workers., Studies done in South Africa reported the highest good healthcare waste management practices with a value of 54.34% (95% CI: 48.05, 60.63), I2 = 0.00%, P < 0.00. The pooled estimate of good healthcare waste management practices before the occurrences of COVID-19 pandemic was 50.49% (95% CI: 40.7, 60.25), (I2 = 97.9%, P < 0.000). Public health facilities also reported having lower waste management practices with a value of 46.86% (95%CI: 39.33, 54.38%), I2 = 96.8%, P < 0.000. Conclusions This review showed that only half of the healthcare workers practiced good healthcare waste management practices. Sex of the healthcare workers, training status, use of working manuals/guidelines, knowledge towards healthcare waste management, and their daily working hours were factors significantly associated with healthcare waste management practices among healthcare workers. Hence, respective healthcare authorities should develop and implement different healthcare waste management strategies, including ongoing in-service training, provision of healthcare waste management manuals, and conducting regular monitoring to enhance healthcare workers’ knowledge and practices towards healthcare waste management practices.